Evaluasi fertilitas, daya tetas, dan kualitas DOD dari itik Alabimaster, Mojomaster, dan Mojomaster x Alabimaster - Tatan Kostaman; Dewi Sari Kumalawati; Soni Sopiyana; Maijon Purba (Universitas Sebelas Maret, 2021)
Objective: The evaluating of the fertility, hatchability, and DOD quality of the ducks selected by the Indonesian Research Institute for Animal Production (Balitnak) consisting of Alabimaster, Mojomaster, and Mojomaster x Alabimaster (MASTER) ducks.Methods: The research was conducted at the Ducks Cage Complex, Balitnak. Using 9,388 Alabimaster duck eggs, 1,635 Mojomaster duck eggs, and 7,638 Mojomaster x Alabimaster (MASTER) duck eggs. The variables observed included fertility, hatchability, and DOD quality. The DOD criteria chosen were healthy, agile, not blind, not disabled, not weak, not wet, and not omphalitis. Completely Randomized Design (CRD) was used and the calculation of the average data for all variables was processed with the help of the SPSS 25.0 program. If there is a difference in value, then the test is carried out with the Duncan Multiple Range Test.Results: The fertility percentage of Alabimaster, Mojomaster, and MASTER ducks did not show any difference (P>0.05) but seen from the relatively high percentage value because it gave a figure of 94%. The percentage of hatchability was significantly different (P<0.05) for the three ducks. The percentage of DOD that passed the selection, MASTER ducks gave a higher value than the other two ducks. The ratio of male and female cubs for the three ducks showed that there were more male than female cubs, but still within the normal range.Conclusions: The average fertility, hatchability, and DOD selected from the hatching eggs of Alabimaster, Mojomaster, and MASTER ducks resulted from the research being quite good.